And Everything Nice: Girls, Aggression, and the Nineteenth-Century British Novel. - Byler, Lauren. (2017)
Abstract: This dissertation investigates the aggression variously expressed by and directed at girls in several nineteenth-century British novels. In doing so, it traces the girl's doubled role in the novel and nineteenth-century culture as a socio-historical subject position and a trope for failure and contradiction that certain novelists map onto this subject position. The girl's highly elastic subjectivity stretches in age and sex, bringing into question the assumption of a clearly-bounded human subject and thus vexing the nineteenth-century novel's promissory cover stories of developmental progress and replete personhood. I argue that Jane Austen, Charles Dickens, Anthony Trollope, and George Eliot each use the girl in distinctive but related ways to indicate fissures in dominant literary and cultural narratives and to figure discrepancies in their most cherished novelistic preoccupations. As a means of illustrating this latter point, every chapter considers (through texts including letters, illustrations, and autobiographical documents) the similar behaviors and fascinations of particular girl characters and their authors, drawing out the writers' concerns with their own repetition of the girl's affective, ethical, and pedagogical failures and successes. These novelists interrogate the sacrosanct Victorian values of maturity, self-abnegation, usefulness, and sympathy through the figure of the girl, whether in her dexterous capacity for deploying covert aggression or in the abject sentimentality of her uselessness and naïveté. The girl's niceness--her socially prescribed selflessness, purity, and tractability--like the girl herself, is a doubled and sometimes duplicitous thing. She encapsulates and complicates the nice distinctions between unadulterated goodness, self-consciously well-mannered conduct, and noxious banality that the nineteenth-century novel cannot quite uphold.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of English.; Advisor: Joseph Litvak.; Committee: Sonia Hofkosh, Lee Edelman, and Rosemarie Bodenheimer.; Keywords: Literature, Gender studies, and Women's studies.